Heterogeneous and Average Effects of the Adoption of Sustainable Agricultural Practices on the Dietary Diversity of Smallholder Farmers in Burkina Faso - Lwungili Justin Bationo; Adiaratou Diallo; Guiro Jeudi Topan (Food and Energy Security)
ABSTRACT The relationship between sustainable agricultural practices and dietary diversity in farm households has recently attracted the attention of development actors and policymakers. We used cross‐sectional data collected from 3704 farmers in the 2021–2022 cropping season to analyze this issue. Using the Probit‐2SLS model that considers endogeneity bias and unobserved heterogeneity, the results reveal that adopting sustainable practices significantly improves the dietary diversity score of smallholders in Burkina Faso. The effect of adopting sustainable agricultural practices is reinforced by access to agricultural extension services, literacy of the head of household, livestock ownership, cultivated area, and agricultural expenditure. In conclusion, the results confirmed the essential role of sustainable agricultural practices in improving the dietary diversity of farm households. The results imply that the interdependent nature of sustainable agricultural practices should be considered when designing effective strategies for disseminating and adopting agricultural practices in Burkina Faso. Our results suggest that different actors in the agricultural sector and the supply chain of agricultural inputs and techniques should consider facilitating access to sustainable agricultural practices for farmers.